Investigation of the relationship between mental health and physical activity among university students - Ahsan, Mohammad; Abualait, Turki (Frontiers in Psychology, 2025)
BackgroundPhysical activity refers to all bodily movement performed by an individual from morning to night. Physical activity benefits not only physical health but also mental health. Physical activity benefits university students in many ways.AimsThis study aimed to determine the effects of physical activity on university students’ mental health.MethodsA cross-sectional study design was conducted with two hundred sixty-five university students. Physical activity level was determined by the International Physical Activity Questionnaire, and mental health among university students was determined using the mental health inventory. Data was collected by online mode. For statistical analysis, the Pearson correlation coefficient test was used, while analysis of variance was used to determine the difference between participants as per their physical activity levels classification. Statistically significant was observed at 0.05 level.ResultsThe results showed that a statistically positive significant relationship existed between physical activity and mental health (r = 0.343, p = <0.001) and its parameters: anxiety (r = 0.542, p = <0.001), depression (r = 0.691, p = <0.001), positive effects (r = 0.476, p = <0.001), behavioral control (r = 0.174, p = 0.004). While comparing the difference between participants as par physical activity level classification, significant differences existed for anxiety (F = 2.96, p = 0.052), depression (F = 4.23, p = 0.041), positive effects (F = 3.22, p = 0.048), behavioral control (F = 3.14, p = 0.058), and mental health (F = 4.65, p = 0.044).ConclusionThe findings suggest that interventions promoting physical activity can serve as effective strategies for mental health promotion in academic settings. Universities should consider integrating structured physical activity programs into their curricula and campus life to leverage these mental health benefits.